Impact of General Anesthesia on Ciliary Functional Analysis by Digital High-Speed Videomicroscopy in Suspected Primary Ciliary Dyskinesia - Lionel Benchimol; Noemie Bricmont; Romane Bonhiver; Grégory Hans; Céline Kempeneers; Philippe Lefebvre; Anne-Lise Poirrier (Diagnostics)
Digital high-speed videomicroscopy (DHSV) is a crucial tool for evaluating ciliary function in children suspected of primary ciliary dyskinesia (PCD). However, until now, samples are taken without anesthesia due to uncertainty about its effect on ciliary function and DHSV interpretation. This study aimed to investigate the impact of general anesthesia on ciliary functional analysis by DHSV in a series of three patients listed for ENT surgeries, which could improve diagnostic procedures for pediatric patients. Patient 1 (7-year-old girl) underwent adenotonsillectomy and tympanostomy placement tube, while patients 2 (17-month-old boy) and 3 (15-month-old girl) underwent adenoidectomy and tympanostomy placement tube. All patients underwent nasal brushing before general anesthesia (control sample). Experimental samples were taken in the contralateral nostril at the time of equilibration of the anesthetic agents (sevoflurane, propofol, sufentanil). Ciliary beat frequency and pattern were measured using digital high-speed videomicroscopy. Our findings highlighted the variability of respiratory ciliary function under general anesthesia among individuals. Our results emphasize the need for caution when interpreting ciliary function data obtained during general anesthesia. Further research with larger cohorts is warranted for validation.